Variable Effect Analysis of Household Characteristics, Family Aware of Nutrition (Kadarzi) and Environmental Sanitation as Risk Factors for Stunting Events (Comparative Study of Agricultural and Non-Agricultural Family in the Regency of South Lampung Regency, 2022) - Berawi, Khairunisa; Pramudyawati, Yustika; Kurniawaty, Evi; Bakri, Samsul; Zuraida, Reni (Budapest International Research and Critics University, 2022)
This study aims to analyze the effect of household characteristics, Kadarzi and environmental sanitation as risk factors for stunting in a comparative study of agricultural and non-agricultural families in South Lampung district. This study uses primary data obtained from questionnaires, that are data of family characteristics, Kadarzi and environmental sanitation from 198 household samples and secondary data, that are data of stunting toddlers and agricultural and non-agricultural areas in South Lampung district in 2022. To achieve the purpose of research, the research method used is observational analytic with a cross sectional approach. The research was conducted from July 2022 to September 2022. The results showed that on the household characteristics variable, variables that had a significant effect were family occupation and family income, while variables that had no significant effect were parents’ education, nutritional knowledge, and gender of children. On the Kadarzi variable, variables that had a significant effect were the behavioral variables of Kadarzi and exclusive breastfeeding, while variables that had no significant effect were variables of weight measurement, various foods, iodized salt and nutritional supplements. On the environmental sanitation variable, the variables that have a significant effect are family latrines, sewerage and agricultural and non-agricultural zones, while variables that have no significant effect are variables of clean water sources and trash bins.